2016
DOI: 10.1155/2016/9612421
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6-174G/C Polymorphism Contributes to Periodontitis Susceptibility: An Updated Meta-Analysis of 21 Case-Control Studies

Abstract: Introduction. Chronic Periodontitis (CP) is suggested to be related to gene variations. Present study aims to quantitatively estimate the association between interleukin-6- (IL-6-) 174G/C polymorphism and CP susceptibility. Materials and Methods. Pubmed, Embase, and Web of Science were searched up to May 2016. The meta-analyses were performed using STATA 12.0. Results. 21 studies were yielded. Significant associations were found under heterozygote comparison and dominant model in studies fulfilling HWE (GC ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…It was demonstrated that the associations between genetic polymorphisms and certain diseases varied with different geographical regions and ethnic groups [ 6 ]. Therefore, we also investigated the contributions of ethnicity to the risk of disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was demonstrated that the associations between genetic polymorphisms and certain diseases varied with different geographical regions and ethnic groups [ 6 ]. Therefore, we also investigated the contributions of ethnicity to the risk of disease.…”
Section: Discussionmentioning
confidence: 99%
“…As we know, interstudy heterogeneity and publication bias are main limitations associated with meta-analyses. Heterogeneity can be caused by many factors such as race, sample sizes, smoking habits, and deviations of allele distributions from the HWE [ 6 ]. There was obvious heterogeneity in the overall analysis involving CP individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, qualitative changes in the levels of these biomarkers could have diagnostic and therapeutic significance. Interleukin 6 (IL-6) is a pro-inflammatory cytokine associated with the severity of periodontitis contributing to bone resorption (Moreira et al, 2007;Graves, 2008;Jaedicke, Preshaw & Taylor, 2016;Zhu et al, 2016). TNF-α is a proinflammatory cytokine that has an effect in the activation of inflammatory leukocytes, modification of vascular permeability and induction of bone resorption (Assuma et al, 1998;Varghese et al, 2015) and is a main inducer of IL-6 (Katz, Nadiv & Beer, 2001).…”
Section: Introductionmentioning
confidence: 99%